Forms of Experimentation in Presenting Contemporary Body Language : A Dream in Baghdad as a Model - HAMMOOD, JAWAD SADIQ (Journal of Tikrit University for Humanities, 2023)
The theatrical form of the Iraqi production "A Dream in Baghdad" was influenced by the results of experimentation, as shown by the director, Anas Abd al-Samad. The researcher conducted an investigation on the aforementioned issues and afterwards organized them into four distinct chapters. The second part of this study encompasses the establishment of terminology. It is structured as the theoretical framework, which has been further separated into two distinct components. In the third chapter, the researcher delineated the research community, explicated the methodology used for sample selection (specifically, a dream in Baghdad), conducted an analysis of the sample, and ultimately presented the salient findings derived from the sample analysis. In relation to the fourth chapter, the researcher will provide the significant findings derived from their investigation and the corresponding conclusions that have been drawn. The researcher provided a comprehensive collection of suggestions, proposals, a compilation of sources, references, and a bilingual summary of the study.